Evaluasi Program Penanggulangan Kejadian Luar Biasa Infeksi Daerah Operasi Pasca SC di Departemen Obsgin RSCM - Surahman Hakim (Center for Health Policy and Management, 2017)
ABSTRACTBackground: Surgical Site Infection (SSI) is one of the complication of surgery that disturbing, both in the patient nor the doctor and the hospital as a health care provider. There is an increased incidence of SSI post-Cesarian Section in the Department of Obstetric and Gynecology in August 2014 ie from the range of 0.16% - 0.33% to 2.32%, whereas RSCM standard should not be more than 2%. The hospital has made several efforts in the prevention program of outbreak SSI post-Cesarian Section by some parties concerned, namely the Committee on Hospital Infection Prevention (PPIRS) by IPCN (Infection Prevention Control Nurse).Method: This study uses a realist evaluation with context, mechanism, and outcome. The data is collected by interviews and focus group discussions with related parties as well as conducting a document review and observations. The results of the study were analyzed using content analysis.Result. Using the hypothesis of C-M-O, that the context is correct, however IPCN and infrastructure in operating rooms also provide a big influence in overcoming the problem of IDO, to decrease the incidence of SSI and increased compliance. Conclusion. The program succeeded in reducing the incidence of SSI with an improved C-M-O. Keywords: Surgical Site Infection (SSI), context, mechanism, outcome, realist evaluation ABSTRAKLatar belakang: Infeksi Daerah Operasi (IDO) merupakan salah satu komplikasi tindakan operasi yang sangat mengganggu, baik dari sisi pasien maupun dokter dan rumah sakit sebagai penyedia layanan kesehatan. Terjadi peningkatan insiden IDO pasca-SC di Departemen Obstetri dan Ginekologi pada bulan September 2014 yaitu dari kisaran 0,16% - 0,33% menjadi 2,32%, sedangkan ambang di RSCM tidak boleh lebih dari 2%. Rumah sakit telah melakukan beberapa upaya dalam program penanggulangan KLB IDO pasca-SC oleh beberapa pihak yang terkait, yaitu Panitia Penanggulangan Infeksi di Rumah Sakit (PPIRS) oleh IPCN (Infection Prevention Control Nurse).Metode: Penelitian ini menggunakan metode realist evaluation dengan pola context, mechanism, dan outcome. Pengumpulan data dilakukan dengan wawancara dan FGD kepada pihak terkait serta melakukan telaah dokumen dan observasi. Hasil penelitian dianalisis menggunakan analisis isi.Hasil: Dengan menggunakan hipotesis C-M-O, bahwa context sudah tepat, mechanism selain peran IPCN, sarana dan prasarana di ruang-ruang operasi juga memberikan andil yang cukup besar dalam penanggulangan masalah IDO, danoutcome terjadi penurunan angka kejadian IDO dan peningkatan kepatuhan.Kesimpulan: Program berhasil menurunkan kejadian IDO dengan C-M-O yang sudah disempurnakan. Kata Kunci: IDO, context, mechanism, outcome, realist evaluation